DISASTER RESILIENCE OF ARTS-AND-CULTURAL-BASED CREATIVE INDUSTRIES (THE CASES OF LOMBOK AND YOGYAKARTA) - Krismiyaningsih, Eri
This research is motivated by the phenomenon of the development of the creative industries which play an important role in regional economic growth. The existence of creative industries that are spread to almost all parts of Indonesia is a great potential as well as a challenge due to the threat of disaster in most parts of Indonesia. To deal with the impact of disasters, creative industries need to build efforts to restore their economic conditions while at the same time maintaining the sustainability of their activities by building resilience. With their creativity, the creative industry should have more ability to build resilience. In previous studies, research still focused on digital technology-based creative industries that developed in urban areas and were threatened by market uncertainty. Research with the characteristics of creative industries in Indonesia, which are mostly creative industries based on traditional arts and culture that tend to be located in rural areas, has not been considered. This study aims to identify how the creative industry is able to build post-disaster creative resilience. The theoretical basis of this research is built on the concepts of creative industry, post-disaster resilience, and creative resilience. With a qualitative approach, this research takes a case study on a creative industry based on traditional rural arts and culture in Bayan Village, Pringgasela Village, and Kasongan Region. The data collection method was carried out through interviews and qualitative analysis was carried out using pattern matching, comparative, and explanation building techniques. This research produces a new concept of creative resilience. The results of the analysis show that the creative resilience process in the creative industry can be achieved by taking into account the inherent capacity, adaptive capacity, and post-disaster adaptive conditions. Creative industries based on traditional arts and culture have inherent and adaptive capacities that tend to be the same as creative industries based on digital technology. However, arts and culture-based creative industries have other supporting capacities, such as cultural preservation and empowerment, which are special motivations for building creative industry resilience. The impact of the disaster did not have a significant effect even thoughiv it caused damage to business buildings, because market conditions were outside the affected area. This research can provide recommendations for regional development, especially in the development of post-disaster creative industries. The discussion of this research is still limited to the threat of eventual disasters and has not paid attention to the threat of continuous disasters and the spatial context of creative industry locations. Therefore, further research on these two topics can be carried out in the future.